Mystus velifer, a new species of catfish from Indochina (Teleostei: Bagridae) - Ng, Heok Hee (Zootaxa, 2012)
Mystus velifer, a new species of catfish from the lower reaches and estuaries of river drainages in mainland Southeast Asiais described here. It can be distinguished from congeners in having a combination of a produced, narrow snout, large eye(diameter 23.3–29.2% SL), the (anterior) cranial fontanel reaching past midway between the posterior orbital margin andthe base of the supraoccipital spine, very long maxillary barbels that reach to or beyond the base of the caudal fin, headlength 24.1–27.6% SL, length of dorsal spine 16.6–21.2% SL, 22–29 rakers on the first gill arch, the first dorsal-fin rayproduced and reaching to the middle of the adipose-fin base, a short-based adipose fin (13.0–17.9% SL) without a deeplyincised posterior margin, and depth of caudal peduncle 8.3–11.1% SL. The synonymy of M. armiger with M. wolffii is confirmed.